PERAN DAN FUNGSI PENDAMPING DESA DALAM SIKLUS PERENCANAAN DESA PASIR MUKTI KECAMATAN CITEUREUP KABUPATEN BOGOR - Janthy Hidayat (Rural Development For Economic Resilience (RUDENCE), 2023)
Pasir Mukti Village, Citeureup District, Bogor Regency has village and community characteristics that are still rural in nature with relatively low levels of education and community welfare. This village has the potential for natural resources and a high productive age workforce to be developed. In addition, the strategic location of Pasir Mukti Village has consequences for the potential for rapid development dynamics that could occur in the future. Law no. 14 of 2014 concerning Villages encourages every village, including Pasir Mukti Village, to be able to develop their own village development plans based on development needs by involving the participation of the community and all stakeholders. One of the main causes of village development plans not being in accordance with village needs and problems is the lack of capacity of village human resources/village facilitators in assisting communities in the participatory development planning process. This community service activity (PkM) aims to provide training to village communities as potential village facilitators as an effort to create a sense of belonging and build a bigger village, which ultimately has an impact on producing development planning programs that suit the needs of the community. The results of the training showed an increase in knowledge and techniques/skills for village assistant candidates as seen from an increase in post-test scores of 53.2% compared to pre-test scores. It was concluded that this PkM activity brought benefits to the people of Pasir Mukti Village, apart from increasing knowledge, other benefits in the long term were more effective village planning and development, as well as increased income and welfare of the people of Pasir Mukti Village. This activity also received a good response from the community and is expected to continue in the future. Keywords: village facilitator, community participation, mentoring, village development plan